206k views
3 votes
Someone please solve this 3n+9n=-2(7-4n)-(1+n)

User Derevo
by
4.9k points

2 Answers

2 votes

Answer:

n=-3

sorry no steps

User Jerad Rose
by
4.7k points
2 votes

Answer:

n= -3

Explanation:


3n+9n=-2(7-4n)-(1+n)\\\\\mathrm{Add\:similar\:elements:}\:3n+9n=12n\\\\12n=-2\left(7-4n\right)-\left(1+n\right)\\\\\mathrm{Expand\:}-2\left(7-4n\right)-\left(1+n\right):\quad 7n-15\\\\12n=7n-15\\\\\mathrm{Subtract\:}7n\mathrm{\:from\:both\:sides}\\\\12n-7n=7n-15-7n\\\\Simplify\\\\5n=-15\\\\\mathrm{Divide\:both\:sides\:by\:}5\\\\(5n)/(5)=(-15)/(5)\\\\Simplify\\\\n=-3

User SDsolar
by
4.4k points